Usefulness of Serum Calcium in the Risk Stratification of Midterm Mortality among Patients with Acute Coronary Syndrome. (3rd November 2019) - Gu, Xingbo; Ding, Xiaotong; Sun, Hongna; Chen, Ningning; Liu, Dandan; Sun, Dianjun; Wang, Shu
Abstract : Serum calcium has been reported to be a predictor of short-term prognosis; however, evidence regarding its association with midterm mortality is scarce. We investigated the association between serum calcium levels at admission and midterm mortality in a retrospective cohort of 2594 consecutive patients with acute coronary syndrome (ACS) who presented to the First Affiliated Hospital of Harbin Medical University from November 2014 to December 2016. Patients were assigned to 4 groups according to the quartiles of serum calcium levels (Ca- Q 1–4) and were followed longitudinally for the time to all-cause death. During a median follow-up period of 21.8 months (17.5∼29.5, IQR), 124 patients died (4.8%) of all causes. Kaplan–Meier curves showed that the incidence of midterm mortality differed significantly (log-rank P = 0.038 ) among the quartiles of serum calcium levels at admission. After adjustment for the confounders that were significant in the univariate analysis, the hazard ratios for the lowest quartile of serum calcium was 1.86 (95% CI, 1.05–3.31; P = 0.033 ), compared with the third quartile (reference group). A multiple restricted cubic spline regression model suggested a reverse J-shaped association between serum calcium levels and midterm mortality, and the lowest risk of mortality was associated with approximately 2.32 mmol/l of serum calcium. In conclusion, the serum calcium level is an independent predictor of all-cause midterm mortality among ACS patients. Patients with abnormal serum calcium levels at admission need more targeted treatments.